The difficulties faced by English teachers in implementing authentic listening material in their classrooms for primary stage students - Ahmad, Zainab Salem (Journal of Educational and Psychological Sciences, 2019)
This study aimed to identify the obstacles of using audio material in the classroom, from the point of view of the teachers of the English language for the basic stage in the north and central Jordan. The study followed the descriptive approach and applied the questionnaire as a data collection tool. The study populations are the male teachers and female teachers of the basic stage in the northern and central governorates during the second semester 2018/2019. The study sample was randomly selected. The results of the study of the obstacles of the use of the original audio material in the classroom showed that there are statistically significant differences at the level of significance of a = 0.5, which is very much related to the learners. The difficulties are increased when the number of students in the classroom increases. Also, these obstacles are related to gender. While there are no statistical differences at the level of significance of a = 0.05 due to the years of experience or maintenance or the difficulty of evaluation or curriculum.